Kur'ân'ın Mekke döneminde korunmasında kitabetin rolü semantik bir analiz çalışması - MOHAMMED, HASAN YOUSİF (Fırat Üniveristesi, 2023)
Bu çalışma, nübüvvetten önce yazı meselesini temellenlendirmeyi, keşfedilen yazıtları ve eski eserleri ve o dönemde yazının amaçlarını aydınlatarak nübüvvetten en az üç asır önce Araplarda hat ve yazı bilincinin var olduğunu, Arapların özellikle Mekke ve Medine'deki kültürel durumun zannedildiği kadar vahim bir durumda olmadığını ortya koymayı amaçlamaktadır. Çalışma, Arap kültüründe sözlü hitaptan yazılıya geçiş noktasını temsil ettiği için Kuran'ın metinleşme sürecinin önemini, özellikle Kur'anî deliller aracılığıyla Mekke döneminde yazının varlığını, yazı ile ilgili Kur'ânî kelime kavramların yanısıra Arap-İslam tarih ve kültürünin verileri üzerinden temellendirererk kanıtlamıyı hedeflemektedir. Bu çerçevede çalışmada, Kuran'ı koruyan bir nesil oluşturmaya ne kadar önem verdiğini göstermek için, Hz. Peygamber'in bu korumayı hangi yöntemlerle gerçekleştiridğine işaret edilmiştir. Bilhassa Peygamberin kendisisnin yazıların doğruluğunun incelemesi ve değerlendirmesi, ayetlerin ve nazil olan sûrelerin yerlerinin tespit etmesi gibi hususlara yer verilmek suretiyle yazıyla muhafaza sünnet ve siretten deliller ışığında detaylı olarak incelenmiştir. Bu çalışma aynı zamanda Kuran'ı Kerim'in ancak hicretten sonra yazıldığını söyleyenlere de cevap olacak kanıtlar barındırmaktadır. Özellikle yazı gereçlerinin o dönemde ilgilenenleri arasında son derece yaygın, kullanışlı ve gelişmiş olduğu ortaya konmuştur.Nitelkim, nüzulünden itibaren Kur'an deri, parşömen, kağıt, ve benzeri yumuşak şeyler üzerine yazılmıştır. Çalışmada ayrıca Kur'an'ı Mekke'den Medine'ye nakledenl sahabilere atıfta bulunarak Kur'an'ın metinleşmem tarihinde büyük rolü kişilere de ışık tutmuştur.

The objective of research is the root the issue of writing before the prophetic mission; by explaining the purposes of writing that existed at the time, by using the inscriptions and discovered monuments. that is for prove that the awareness of calligraphy and writing, it was present among the Arabs at least three centuries before the mission, and the cultural situation of the Arabs, especially in the both city Mecca and Medina, is not in a deplorable position. The research also proves its existence in the Meccan epoch through the Quranic evidence by mentioning its meanings and indicating its importance by studying the Quranic roots related to writing in terms of; the number of iterations, the multiplicity of its forms, and its fields; To show the extent of the Quran's interest in writing, as it represents the turning point of the Arabs from oral to written. As well as the evidence from the Prophet's Sunnah to show the extent of the care of the Messenger (may God bless and grant him peace); and also through the building a generation that preserves the Quran, by explaining the details of the methods of preservation, and supervising the writing, and verifying the authenticity of the written by reviewing it to straighten it, and repair it from falling off, and also to determine the places of the revealed verses and suras; lastly Using evidence from biography and history. The research also aims responding to those who say that the Holy Quran was not written until after the Prophet's migration, with textual and mental evidence, to refute their suspicions about the integrity of the Quranic text, and that the popular saying; That writing was not on soft and easy-to-carry tools represents only part of the truth, and that the Qur'an was written on these soft tools; From leather, parchment, leaf, and paper... This is in order to clarify the fate of the written of the Holy Quran in Makkah, and to identify the methods used by them to transfer this written from Makkah to Madinah, by referring to the names of those who carry out such a great task. Keywords: The Hıstory of Quran, Preservation, Writing tools, Rooting, Semantics
Keywords: Din